Immunoglobulin-Y Effect On Protein Of Streptococcus Mutans Isolated From Caries And Caries-Free Subjects - Aditiya Irwandi, Rizky; Winiati Bachtiar, Endang; Yuniastuti, Mindya (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2012)
The main microbial culprit in dental caries is Streptococcus mutans (S.mutans),virulence of which can be observed by its differential protein expression betweencaries and caries-free subjects.The success of Immunoglobulin-Y (IgY) antiS.mutans as a passive immunization agent in eliminating S.mutans has beenreported. The aim of this study is to analyze the effect of IgY anti S.mutans on theprotein expression of S.mutans isolated from caries and caries-free subjects. Eachdental plaque was collected by swabbing the buccal surface of the first lowerpermanent molar of caries and caries-free subjects. The plaques were thencultured on agar medium TYS20B. After 72 hours, the colonies from each of themwere cultured in liquid medium TYS Broth for 72 hour. Each collected bacteria(whether from caries or caries-free subjects) were grouped into control andexposure group. In exposure group, S.mutans was exposed by pre-incubated (forone hour at 37Â°C) IgY anti S.mutans for one hour at 37Â°C. Protein expression ofS.mutans was analyzed with SDS PAGE after the preparation of its antigen andBradford protein assay. Our result shows that S.mutans 41.3 kilodalton proteinexpression of caries subjects, are up-regulated in comparison to the control group.Meanwhile, the S.mutans 41.3 kilodalton protein expression of caries-freesubjects, are down-regulated in comparison to the control group. This studysuggests that IgY anti S.mutans up-regulates 41.3 kilodalton protein expression ofS.mutans in the caries subjects. However IgY anti S.mutans down-regulates 4.13kilodalton protein expression of S.mutans in the caries-free subjects.